105 Broadening the clinical spectrum of bortezimib induced peripheral neuropathy: 4 illustrative cases. Issue 6 (27th May 2022) - Grundy, Kristina; Keh, Ryan; Power, Rachael; Gosal, David; Lavin, Tim
Abstract : Bortezomib is a proteasome inhibitor, used in the treatment of multiple myeloma. Bortezimib induced peripheral neuropathy (BIPN) is classically a painful, sensory predominant, length dependent axonal neuropathy [1]. Atypical presentations including demyelinating neuropathies can occur, though rarely (2]. We identified 4 patients from the Manchester Centre for Clinical Neuroscience with atypical BIPN. All 4 had multiple myeloma and developed symptoms within 2 cycles of intravenous treatment. Case 1 and 2 developed proximal and distal motor weakness and neuropathic pain. Neurophysiology confirmed mixed demyelinating/axonal neuropathy in both. Cerebral Spinal Fluid analysis confirmed albuminocytological dissociation. Immunomodulatory treatment with IVIg and steroids had minimal effect. Case 3 developed left hand weakness, predominantly affecting the radial musculature with motor conduction block on neurophysiology. Case 4 developed whole body paraesthesias, ataxia and thoracic radicular pain after 2 cycles, neurophysiology confirmed a sensory neuronopathy. Case 2 died due to disease progression, the other 3 cases improved on withdrawal of Bortezimib. Conclusion: BIPN can cause neuropathy phenotypes including sensory neuronopathy, motor neuropathy with conduction block and severe demyelinating polyradiculoneuritis. Immunogenic, as well as toxic mechanisms may have a role in the pathogenesis of BIPN. 1. Chaudhry V, Cornblath D, Polydefkis M, Ferguson A, Borrello I. Characteristics of bortezomib- and thalidomide-induced peripheral neuropathy. Journal of the Peripheral Nervous System. 2008;13(4):275–282 2. Thawani S, Tanji K, De Sousa E, Weimer L, Brannagan T. Bortezomib-Associated Demyelinating Neuropathy—Clinical and Pathologic Features. Journal of Clinical Neuromuscular Disease. 2015;16(4):202–209 tim.lavin@srft.nhs.uk